Low‐dose aspirin reduces uteroplacental vascular impedance in early and mid gestation in IVF and ICSI patients: a randomized, placebo‐controlled double‐blind study - Haapsamo, M.; Martikainen, H.; Räsänen, J. (Ultrasound in obstetrics & gynecology, 2008)
Objective To determine whether low‐dose aspirin improves uteroplacental hemodynamics in unselected in‐vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) subjects when medication is started concomitantly with controlled ovarian hyperstimulation. Methods Thirty‐seven pregnant women who had undergone IVF/ICSI and had been randomized to receive 100 mg aspirin (n = 17) or placebo (n = 20) daily, started concomitantly with controlled ovarian hyperstimulation, were included in this study. Doppler ultrasound examination was performed at 6, 10, 13 and 18 weeks' gestation. Uterine artery (UtA) pulsatility index (PI) was calculated and bilateral UtA notching was noted. Subplacental arcuate artery PI was obtained at 6 and 10 weeks' gestation. Umbilical artery (UA) PI and mean velocity were calculated at 10, 13 and 18 weeks' gestation. In the aspirin group there was one early pregnancy miscarriage, and one patient discontinued the study medication owing to early pregnancy bleeding. A total of 15 women in the aspirin group and 20 women in the placebo group underwent the complete ultrasound protocol. Results At 6 weeks' gestation, arcuate artery PI and at 18 weeks' gestation, UtA PI were lower (P < 0.05) in the aspirin group than in the placebo group. At 18 weeks' gestation, bilateral UtA notching tended to be more common in the placebo group (40%) than in the aspirin group (13%) (P = 0.06). UA PI and mean velocity did not differ significantly between the groups. Conclusion Low‐dose aspirin reduces uteroplacental vascular impedance in early and mid pregnancy in unselected IVF/ICSI subjects when medication is started concomitantly with controlled ovarian hyperstimulation. Copyright © 2008 ISUOG. Published by John Wiley & Sons, Ltd.